A robust two layer green supply chain modelling under performance based fuzzy game theoretic approach. (February 2021) - Bhattacharya, Kousik; De, Sujit Kumar
Graphical abstract: Note: PCM = Pollution Control Measure. Highlights: Sponge iron manufacturing problem is considered. Pollution due to production and transportation of items is considered. Game theory with and without performances are considered. Fuzzy logic is employed. Abstract: This article deals with a pollution sensitive production-transportation supply chain (SC) model with backorder under three-layer marketing executives' performance based fuzzy strategic game approach. Each executive group follows a cycle time dependent performance function according to some rules. Considering a real case study, we develop a cost minimization centralized two-layer SC model under the effect of pollution. The amount of pollution is estimated by percentage via some pollution function studied for the emissions of carbon dioxide (CO2 ) during industrial production and road transportation. We split the original problem into equivalent game problem in which the producer (vendor) plays the role of player 1 in one side and the buyer (customer) plays the role of player 2 in the other side exclusively. The game problem is studied under different scenarios namely performance indices, game strategy and with and without pollution measures. Utilizing the data set of case study over sponge iron industry we perform some numerical computations with the help of LINGO software. Our findings reveal that, whenever the Gaussian probabilistic strategies with row interchanging performance matrix is employed on numerical illustrations then the centralized SC cost gets minimum with reduced pollution level. Finally, a comparative study, sensitivity analysis and graphical illustrations are done to justify the robustness of the proposed model.